Assessing electric vehicle distributed energy resource potential and transport energy requirement constraints - Mills, Graham; MacGill, Iain (Proceedings / IEEE Power Engineering Society General Meeting, 2014)
One source of potential benefit for the electricity industry from the integration of electric vehicles is the potential for the aggregate storage within vehicle batteries to act as a Distributed Energy Resource to assist power system operation. This resource however, is subject to a set of constraints related to both the availability of recharging infrastructure and the underlying transport needs of vehicle owners. This paper explores the impact of charging infrastructure availability and vehicle travel requirements on the temporal Distributed Energy Resource potential characteristic. In particular, a method of constructing a vehicle Transport Energy Requirement Constraint from existing Battery State of Charge profiles and vehicle trip information is introduced and applied in a case study of vehicle travel in the Sydney Greater Metropolitan Area to illustrate the results obtained. The availability of recharging infrastructure is found to have a significant impact on both the temporal characteristic of Transport Energy Reservation requirement and the Distributed Energy Resource potential available to the power system from electric vehicle batteries.